Giải hệ phương trình: $\left \{ {{x + 2y – xy – 2 = 0} \atop {x^{2} – y^{2} + 2x^{2}y + 2xy^{2} + 1 = 0}} \right.$

Question

Giải hệ phương trình: $\left \{ {{x + 2y – xy – 2 = 0} \atop {x^{2} – y^{2} + 2x^{2}y + 2xy^{2} + 1 = 0}} \right.$

in progress 0
Everleigh 5 tháng 2021-07-16T07:16:08+00:00 2 Answers 4 views 0

Answers ( )

    0
    2021-07-16T07:17:09+00:00

    Đáp án:

    $S =\left\{(2;-1);\left(2;-\dfrac53\right);(0;1);\left(-\dfrac23;1\right)\right\}$

    Giải thích các bước giải:

    $\quad \begin{cases}x + 2y – xy – 2 = 0\\x^2 – y^2 + 2x^2y + 2xy^2 + 1 = 0\quad (*)\end{cases}$

    $\Leftrightarrow \begin{cases}(x-2)(y-1)= 0\\x^2 – y^2 + 2x^2y + 2xy^2 + 1 = 0\end{cases}$

    $\Leftrightarrow \begin{cases}\left[\begin{array}{l}x= 2\\y = 1\end{array}\right.\\x^2 – y^2 + 2x^2y + 2xy^2 + 1 = 0\end{cases}$

    +) Thay $x = 2$ vào $(*)$ ta được:

    $\quad 2^2 – y^2 + 2.2^2y + 2.2y^2 + 1 = 0$

    $\Leftrightarrow 3y^2 + 8y + 5 = 0$

    $\Leftrightarrow \left[\begin{array}{l}y = -1\\y = -\dfrac53\end{array}\right.$

    +) Thay $y =1$ vào $(*)$ ta được:

    $\quad x^2 – 1^2 + 2x^2.1 + 2x.1^2 + 1 = 0$

    $\Leftrightarrow 3x^2 + 2x = 0$

    $\Leftrightarrow \left[\begin{array}{l}x = 0\\x =-\dfrac23\end{array}\right.$

    Vậy $S =\left\{(2;-1);\left(2;-\dfrac53\right);(0;1);\left(-\dfrac23;1\right)\right\}$

    0
    2021-07-16T07:18:06+00:00

    $\begin{cases} x+2y-xy-2=0\\x^2-y^2+2x^2y+2xy^2+1=0 \ \ (1)\end{cases}$

    $\Leftrightarrow \begin{cases}(x-2)(y-1)=0\\x^2-y^2+2x^2y+2xy^2+1=0\end{cases}$

    $\Leftrightarrow \begin{cases} \left[ \begin{array}{l}x=2\\y=1\end{array} \right.\\x^2-y^2+2x^2y+2xy^2+1=0\end{cases}$

    `+)` Thay `x=2` vào `(1)` ta có :

    `2^2-y^2+2.2^2 y+2.2.y^2+1=0`

    `<=> 4-y^2+8y+4y^2+1=0`

    `<=> 3y^2+8y+5=0`

    `<=> 3y^2+3y+5y+5=0`

    `<=> 3y.(y+1)+5.(y+1)=0`

    `<=> (3y+5).(y+1)=0`

    `<=>` \(\left[ \begin{array}{l}y=-\dfrac{5}{3}\\y=-1\end{array} \right.\) 

    `+)` Thay `y=1` vào `(1)` ta có :

    `x^2-1^2+2x^2 . 1+2x . 1^2+1=0`

    `<=> x^2-1+2x^2+2x+1=0`

    `<=> 3x^2+2x=0`

    `<=> x.(3x+2)=0`

    `<=>` \(\left[ \begin{array}{l}x=0\\x=-\dfrac{2}{3}\end{array} \right.\) 

    Vậy tập nghiệm của hệ phương trình là : 

    `S = { ( 2 ; -5/3 ) ; ( 2 ; -1 ) ; ( 0 ; 1 ) ; ( -2/3 ; 1 ) }`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )